O uso de tecnologias digitais na alfabetização: concepções de professores da escola pública - Trajano, Jonh Herbert de Almeida Falcão (2019)
This qualitative research aims to understand the place of digital technologies from the perspective of literacy teachers. Theoretically, this work is based on studies by Dudeney, Hockly, Pegrum (2016), which bring the definition of “digital literacy”, Rojo (2012) that discusses the “multiliteracy” and how to make it part of contemporary school learning, Frade (2004) and Gloria (2012; 2015) talk specifically about how to adapt literacy to the use of digital technologies and Moran (2013) that discusses the ways in which teachers mediate technological-digital resources in school. Methodologically our investigative course started from three procedures: 1) Application of a meaning representation technique for the term digital technologies with teachers of the literacy cycle, from João Pessoa's public school; 2) Conducting recorded interviews with literacy teachers of 01 State school and 02 municipal schools in the city of João Pessoa - PB; 3) Observation with filmed record of the practice of three teachers in a moment of utilization of technological resources (computer lab, etc.) in the school. The corpus of this research, therefore, is organized from the data raised in these three methodological procedures. This research was attended by 17 literacy teachers who were divided into three groups. The first group had seven teachers from the literacy cycle from a teaching education event in the city of João Pessoa, who participated in the technique of meaning representation. The second group had 06 teachers from a state school in Bairro dos Estados, 03 teachers from a municipal school in Grotão, and 01 teacher from a municipal school in the Bairro dos Novais, in João Pessoa; this group of ten teachers participated in the individual interviews. The third group had 03 teachers (02 from the municipal school in Grotão, and 01 from the municipal school in Bairro dos Novais), who also participated in the interviews for the videotaped observation of the practice of using digital-technological resources in the school. From the data of the technique of representation of meanings applied, it can be observed that in the representations of the literacy teachers digital technologies gain meaning from the perspective of reality / context of use that these teachers make of these resources in the school, also presenting low ability in the development of literacy and thus videos, tele-classes and games as usually more accessible and used resources. But even so, these literacy teachers recognize in their representation for this term the need to know and already articulate with the techniques of these new resources, as well as the relevance of digital literacy already in literacy. In the speeches of the literacy teachers during the individual interviews, we highlight those who still feel inhibited in promoting digital literacy in literacy, either due to the lack / absence of digital-technological resources in the school, as was the case reported by the school's literacy teachers. State, as well as, not assisted by a formative public policy to prepare them to think and start with practices that generate multiliteracy in literacy. The analysis of the filming of the practices observed in the labs also reinforces that these literacy teachers are still unable to introduce literacy practices with digital technologies that lead to simultaneous literacy, both in print and in technological-digital media. This would thus generate a multiliteracy circulation space.